2012
DOI: 10.1073/pnas.1209592109
|View full text |Cite
|
Sign up to set email alerts
|

Brain and muscle Arnt-like protein-1 (BMAL1) controls circadian cell proliferation and susceptibility to UVB-induced DNA damage in the epidermis

Abstract: The role of the circadian clock in skin and the identity of genes participating in its chronobiology remain largely unknown, leading us to define the circadian transcriptome of mouse skin at two different stages of the hair cycle, telogen and anagen. The circadian transcriptomes of telogen and anagen skin are largely distinct, with the former dominated by genes involved in cell proliferation and metabolism. The expression of many metabolic genes is antiphasic to cell cycle-related genes, the former peaking dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
325
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 225 publications
(350 citation statements)
references
References 28 publications
20
325
5
Order By: Relevance
“…Consistent with the possible importance of this regulation, clock protein misexpression and/or a lack of circadian control has been documented in multiple tumor types (Hwang-Verslues et al, 2013; Luo et al, 2012;Zhao et al, 2013) and immortalized cell lines (Yeom et al, 2010). In normal physiology, circadian cell division has been documented in adult hippocampal neurogenesis (BouchardCannon et al, 2013), in intestinal and skin epithelial cell division (Geyfman et al, 2012;Janich et al, 2013;Karpowicz et al, 2013), and in multiple immune cell populations (Fortier et al, 2011;Keller et al, 2009) -essentially anywhere that cell division occurs in adult animals.…”
Section: From Cell Cycle To Tissues: Circadian Control Of Tissue Homementioning
confidence: 77%
“…Consistent with the possible importance of this regulation, clock protein misexpression and/or a lack of circadian control has been documented in multiple tumor types (Hwang-Verslues et al, 2013; Luo et al, 2012;Zhao et al, 2013) and immortalized cell lines (Yeom et al, 2010). In normal physiology, circadian cell division has been documented in adult hippocampal neurogenesis (BouchardCannon et al, 2013), in intestinal and skin epithelial cell division (Geyfman et al, 2012;Janich et al, 2013;Karpowicz et al, 2013), and in multiple immune cell populations (Fortier et al, 2011;Keller et al, 2009) -essentially anywhere that cell division occurs in adult animals.…”
Section: From Cell Cycle To Tissues: Circadian Control Of Tissue Homementioning
confidence: 77%
“…In addition to its function in controlling biologic rhythm, Bmal1 is closely related to aging, angiocardiopathy, immune disorders, and cancers (8)(9)(10)(11)(12). Recent evidence suggests that Bmal1 is correlated with proliferation and the cell cycle, indicating that Bmal1 may play an important role in tumorigenesis (11,(13)(14)(15). For instance, Bmal1 has been shown to affect the cell cycle and cell proliferation by regulating the p53/p21 signaling pathway (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…Disruption of the circadian rhythm is linked with deregulated cell proliferation and the progression of cancer (95,96). A large number of animal studies have shown cancer development in animal models of circadian disruption (94,(97)(98)(99)(100). It was reported that both pancreatic carcinoma and osteosarcoma xenografts grew at a faster rate in animals with suprachiasmatic nuclei lesions (101).…”
Section: Cancer Circadian Rhythm Disruption and Tumorigenesismentioning
confidence: 99%
“…This notion has been shown in rapidly dividing cells of skin, gut, pancreas, reproductive organs, and bone marrow in humans and animals (89)(90)(91)(92)(93)(94). Disruption of the circadian rhythm is linked with deregulated cell proliferation and the progression of cancer (95,96).…”
Section: Cancer Circadian Rhythm Disruption and Tumorigenesismentioning
confidence: 99%
See 1 more Smart Citation